PENGEMBANGAN KURIKULUM BAHASA ARAB DI MADRASAH - Roviin . . (Tarling : Journal of Language Education, 2018)
Abstract This article is motivated by the need for the development of Arabic language curriculum in madrasa. Developing Arabic language curriculum in madrasa refers to the Rule of the Minister of Religious Affairs of the Republic of Indonesia, Number: 165 of 2014 on Guidance of Curriculum in Madrasa 2013, Subject of Islamic Education and Arabic Language in Madrasa. In curriculum development, each approach, model and procedure has advantages and disadvantages. However, in the context of Arabic learning in madrasa, the functional approach is more appropriately used with the model of combining all language skills as well as in a theme called the â€œall in one systemâ€/nadhariyya al-wihda. From this approach and model can be realized through a joint procedure between top-down and bottom-up. The content standards for the Arabic language curriculum are thematically constructed for use in four language skills, namely listening (istima'), speaking (kalam), reading (qira'ah) and writing (kitabah). Ù…Ù„Ø®Øµ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ù…Ù‡Ù…Ø© ÙÙŠ Ø§Ù„ØØ§Ø¬Ø© Ø¥Ù„Ù‰ ØªØ·ÙˆÙŠØ± Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©. Ø£Ø³Ø³ ØªØ·ÙˆÙŠØ± Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø¹Ù„Ù‰ Ù‚Ø±Ø§Ø± ÙˆØ²ÙŠØ± Ø§Ù„Ø´Ø¤ÙˆÙ† Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ù„Ø¬Ù…Ù‡ÙˆØ±ÙŠØ© Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ Ø±Ù‚Ù… : 165 Ø§Ù„Ø¹Ø§Ù… 2014 Ø¨Ø´Ø£Ù† Ø¯Ù„ÙŠÙ„ Ø§Ù„Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠØ© 2013 Ù„Ù…Ø§Ø¯Ø© Ø§Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©. Ø¥Ù† ÙÙŠ ØªØ·ÙˆÙŠØ± Ø§Ù„Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠØ© Ù†Ù‡Ø¬ ÙˆÙ†Ù…ÙˆØ°Ø¬ ÙˆØ¥Ø¬Ø±Ø§Ø¡Ø§ØªØŒ ÙˆÙ„Ù‡Ø§ Ù…Ø²Ø§ÙŠØ§ ÙˆØ¹ÙŠÙˆØ¨. ÙˆÙ…Ø¹ Ø°Ù„ÙƒØŒ ÙÙÙŠ Ø³ÙŠØ§Ù‚ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©ØŒ ÙŠØªÙ… Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù†Ù‡Ø¬ Ø§Ù„ÙˆØ¸ÙŠÙÙŠ Ø£ÙƒØ«Ø± Ù…Ù„Ø§Ø¡Ù…Ø© Ù…Ø¹ Ø¬Ù…ÙŠØ¹ Ø§Ù„Ù†Ù…Ø§Ø°Ø¬ Ø¨ÙŠÙ† Ø¬Ù…ÙŠØ¹ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆÙƒØ°Ù„Ùƒ ÙÙŠ Ù…ÙˆØ¶ÙˆØ¹ ÙŠØ³Ù…Ù‰ Ù†Ø¸Ø±ÙŠØ© Ø§Ù„ÙˆØØ¯Ø©. ÙÙ…Ù† Ø§Ù„Ù†Ù‡Ø¬ ÙˆØ§Ù„Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„Ø³Ø§Ø¨Ù‚ ÙŠÙ…ÙƒÙ† Ø£Ù† ØªØªØÙ‚Ù‚ Ù…Ù† Ø®Ù„Ø§Ù„ Ø¥Ø¬Ø±Ø§Ø¡ Ù…Ø´ØªØ±Ùƒ. Ø¥Ù† Ù…Ø¹Ø§ÙŠÙŠØ± Ø§Ù„Ù…ØØªÙˆÙ‰ Ø§Ù„ØªÙŠ ÙŠØªÙ… ØªØ·ÙˆÙŠØ± Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙŠØªÙ… Ø¥Ù†Ø´Ø§Ø¤Ù‡Ø§ Ø¨Ø´ÙƒÙ„ Ù…ÙˆØ¶ÙˆØ¹ÙŠ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ ÙÙŠ Ø£Ø±Ø¨Ø¹ Ù…Ù‡Ø§Ø±Ø§Øª Ù„ØºÙˆÙŠØ© Ù‡ÙŠ Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ ÙˆØ§Ù„ÙƒÙ„Ø§Ù… ÙˆØ§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙˆØ§Ù„ÙƒØªØ§Ø¨Ø©.